2019
DOI: 10.3389/fnins.2019.01342
|View full text |Cite
|
Sign up to set email alerts
|

High-Resolution Transcranial Electrical Simulation for Living Mice Based on Magneto-Acoustic Effect

Abstract: Transcranial electrical stimulation is an important neuromodulation tool, which has been widely applied in the cognitive sciences and in the treatment of neurological and psychiatric diseases. In this work, a novel non-invasive method of transcranial electrical stimulation with high-resolution transcranial magneto-acoustic stimulation (TMAS) method has been tested experimentally in living mice for the first time. It can achieve spatial resolution of 2 mm in the cortex and even in the deep brain regions. The in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 33 publications
0
10
0
Order By: Relevance
“…We have demonstrated that TMAS can be used to generate an electric field in a conductive medium upright to the orientation of the magnetic and sound fields and that the electric field coverage is extremely consistent with that of the acoustic field in our previous work [ 23 ]. TMAS integrates a magneto-acoustic electric field and the mechanical force of TUS [ 22 ]. The mechanical force of TUS may alter ion channels so that electric field stimulation has a much stronger effect.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…We have demonstrated that TMAS can be used to generate an electric field in a conductive medium upright to the orientation of the magnetic and sound fields and that the electric field coverage is extremely consistent with that of the acoustic field in our previous work [ 23 ]. TMAS integrates a magneto-acoustic electric field and the mechanical force of TUS [ 22 ]. The mechanical force of TUS may alter ion channels so that electric field stimulation has a much stronger effect.…”
Section: Discussionmentioning
confidence: 99%
“…S7 and S8 ). In the effective electrical stimulation results of the in vivo study, the electric fields with intensities ranging from 10 to 338 mV/m [ 22 , 63 65 ]. The strengths of the acoustic (0.3 MPa) and electric fields (36 mV/m) produced in our study are both in the range of the effective stimulus parameters.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Behavioral outcome associated with immunofluorescence technique measurements indicated that after 4 days of LI-TUS at M1 with 0.76 W/cm 2 ( I SPPA) in PD mice showed an increase of c-Fos positive cells in M1 as well as superior behavioral performance compared to the sham control group (Zhou et al, 2019a). When the substantia nigra (SN) was stimulated (Zhou et al, 2019b), the stimulated healthy mice did not exhibit significantly different behavior compared to the control mice. However, stimulation of SN in PD mice did induce significant improvement in spatial related forms of motor behavior performance than the control group.…”
Section: Neuromodulatory Effect Of Tus In Animalsmentioning
confidence: 99%